(untitled) (Experimental biology, 2009)
In order to develop genetic map of Yuzhnokazahstanskaya 43 x Hsp line from Israel we have selected polymorphic markers based on PCR (polymerase chain reaction) of 45 AFLP combinations and 57 SSRoligonucleotide primer pairs. The genetic map was consisted from 17 SSR and 50 AFLP markers. The mapping population that consisted from 114 F2 lines of Yuzhnokazahstanskaya 43 x Hsp was analyzed for phenological and agronomic traits. The analysis of mapping population and quantitative data based on ANOVA and QTLCartografer statistical programs were allowed to identify 12 QTLs that associated with drought resistance. Five DNA markers that tightly linked with identified QTLs were suggested to use for programs, which will be associated with breeding of new cultivars for better resistance to drought